Third Year University Students' Reading Habits and Perceptions of Reading for Pleasure: A Descriptive Study - Irma Siti Fatimah; Slamet Wahyudi Yulianto (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2025)
The purpose of this research is to identify students' reading habits and describe their perceptions of Reading for Pleasure (RfP). This research enlisted the participation of eight third-year higher education students studying English Langauge Education as their major in one the universities in Subang, West Java province. Questionnaires and interviews were employed to collect the data. The data were then analysed using thematic analysis. According to the findings, 62.5% of students read once a week, 25% read in their spare time, and 87.5% read on their phones. The benefits of RfP are well acknowledged by students, yet data indicates that reading interest among students is low. As a result, this research highlights the importance of introducing children to books early on and helping them develop an enthusiasm for reading. Based on the numerous benefits of RfP, teachers and parents must be aware of and often socialize about the benefits of RfP. Teachers in schools, as well as parents at home, must then take the initiative and creatively introduce this activity to their children in order for them to develop a love of reading.